Roles of Endothelial Motilin Receptor and Its Signal Transduction Pathway in Motilin-Induced Left Gastric Artery Relaxation in Dogs - Li, HongYu; Yang, LanLan; Jin, Ying; Jin, ChunXiang (Frontiers in Physiology, 2021)
Background: Motilin increases left gastric artery (LGA) blood flow in dogs via the endothelial motilin receptor (MLNR). This article investigates the signaling pathways of endothelial MLNR. Methods: Motilin-induced relaxation of LGA rings was assessed using wire myography. Nitric oxide (NO), and cyclic guanosine monophosphate (cGMP) levels were measured using an NO assay kit and cGMP ELISA kit, respectively. Results: Motilin concentration-dependently (EC50=9.1±1.2×10−8M) relaxed LGA rings precontracted with U46619 (thromboxane A2 receptor agonist). GM-109 (MLNR antagonist) significantly inhibited motilin-induced LGA relaxation and the production of NO and cGMP. N-ethylmaleimide (NEM; G-protein antagonist), U73122 [phospholipase C (PLC) inhibitor], and 2-aminoethyl diphenylborinate [2-APB; inositol trisphosphate (IP3) blocker] partially or completely blocked vasorelaxation. In contrast, chelerythrine [protein kinase C (PKC) inhibitor] and H89 [protein kinase A (PKA) inhibitor] had no such effect. Low-calcium or calcium-free Krebs solutions also reduced vasorelaxation. N-nitro-L-arginine methyl ester [L-NAME; nitric oxide synthase (NOS) inhibitor] and ODQ [soluble guanylyl cyclase (sGC) inhibitor] completely abolished vasodilation and synthesis of NO and cGMP. Indomethacin (cyclooxygenase inhibitor), 18α-glycyrrhetinic acid [18α-GA; myoendothelial gap junction (MEGJ) inhibitor], and K+ channel inhibition through high K+ concentrations or tetraethylammonium (TEA-Cl; KCa channel blocker) partially decreased vasorelaxation, whereas glibenclamide (KATP channel blocker) had no such effect. Conclusion: The current study suggests that motilin-induced LGA relaxation is dependent on endothelial MLNR through the G protein-PLC-IP3 pathway and Ca2+ influx. The NOS-NO-sGC-cGMP pathway, prostacyclin, MEGJ, and K+ channels (especially KCa) are involved in endothelial-dependent relaxation of vascular smooth muscle (VSM) cells.